2001
DOI: 10.1136/bmj.322.7285.529
|View full text |Cite
|
Sign up to set email alerts
|

Just in time information for clinicians: a questionnaire evaluation of the ATTRACT project

Abstract: General practitioners generate many clinical questions during consultations. However, when they seek answers to these queries they tend to rely on colleagues and "desk top" references rather than searching the literature themselves. [1][2][3] ATTRACT was created in 1997 to provide rapid, evidence based summaries to clinical queries. All general practitioners in Gwent were invited to send their clinical queries to ATTRACT. For each query an information manager (JB) undertook a rapid search of the literature. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 5 publications
2
43
0
1
Order By: Relevance
“…It is possible that the responders in the other studies did not assess patient information as a change in clinical practice. Evidence-based answering services for GPs, where clinical questions in general and not only limited to pharmacotherapy are being answered by clinical librarians or GPs have also evaluated the impact on the patient [18][19][20][21]. All these studies promoted the usefulness of an evidence-based answering service, and 20-55% of the GPs reported that the given answers had an effect on their patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the responders in the other studies did not assess patient information as a change in clinical practice. Evidence-based answering services for GPs, where clinical questions in general and not only limited to pharmacotherapy are being answered by clinical librarians or GPs have also evaluated the impact on the patient [18][19][20][21]. All these studies promoted the usefulness of an evidence-based answering service, and 20-55% of the GPs reported that the given answers had an effect on their patients.…”
Section: Discussionmentioning
confidence: 99%
“…15 We are unaware of any published reports of a GP led answering service in the UK. The reasons for choosing a GP as informaticist were threefold 16 : + doctors often ask colleagues for answers to questions [2][3][4] ; + a GP is likely to understand the precise nature and context of the question; + a GP is ideally placed to help a colleague "frame" a question.…”
mentioning
confidence: 99%
“…In agreement with previous studies of general clinical resource use in the medical and allied health professions, physiotherapists primarily used clinical anatomy resources for current patient management. [1][2][3][4]9 More than half of respondents (55%) used clinical anatomy resources at least once per week; the majority (66%) used printed resources more frequently than online resources. However, 85% of physiotherapists in our study used online clinical anatomy resources, a figure higher than that found in a previous study investigating physiotherapists' use of an online clinical resource portal in general hospital practice in New South Wales in 2004 (55%) 2 but similar to rates of use of general clinical resources online by physiotherapists in the United Kingdom in 2013 (85%).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical resources can provide up-to-date information, contribute to decision making, enhance patient care, and facilitate clinical reasoning. [1][2][3][4] The nature of clinicians' use of clinical resources is therefore important because of its potential influence on clinical practice and patient outcomes.…”
mentioning
confidence: 99%